Analisis Strategi Pemungutan Pajak Bumi Dan Bangunan Pedesaan Dan Perkotaan (PPB-P2) Dimasa Pandemi Covid-19 Dalam Meningkatkan Penerimaan Pajak Daerah Pada Badan Pendapatan Daerah Dki Jakarta Tahun 2020 - Devi Rafianti Almis; Khairur Raziqiin (Jurnal Ilmu Administrasi Publik, 2021)
The target and realization of PBB-P2 revenue in 2020 decreased by only 94.79% compared to the previous year. The target and realization of tax revenue are ideally expected to increase from year to year. This study aims to analyze the strategies of rural and urban land and building tax (PBB-P2) collection during the Covid-19 pandemic in increasing the regional tax revenue at the DKI Jakarta regional revenue agency in 2020. The researcher used a qualitative approach with a descriptive type of research. The data employed in this study included secondary data obtained from the literature study and primary data obtained from interviews. The data analysis techniques used were data reduction, data display, and drawing conclusions from a model proposed by Miles and Huberman (1984). The findings of this study were: (1) the strategies conducted is based on the theoretical approach of Koteen's types of strategies, including by carrying out the digital transformation in the form of e-SPPT or the electronic Notification of Tax Due, expanding PBB-P2 payment channels through e-Commerce, improving the quality of supporting resources, providing online dissemination and counseling, and providing policies of PBB-P2 exemption and reduction; (2) The inhibiting factors experienced are the decline in taxpayer income which affects the ability to pay taxes, the existence of Large-Scale Social Restrictions (PSBB) and Community Activity Restrictions (PPKM), and programs planned for normal conditions which do not run optimally; (3) Efforts that can be made to overcome these issues include implementing the policies of PBB-P2 exemption and reduction, providing dissemination, counseling, and education, and communicating online via WhatsApp for taxpayers to facilitate the issuance of SPPT and other letters in 2020.